The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1995
DOI: 10.1046/j.1469-0705.1995.06010015.x
|View full text |Cite
|
Sign up to set email alerts
|

Blood flow velocity waveforms of the abdominal arteries in appropriate‐ and small‐for‐gestational‐age fetuses

Abstract: The aim of this study was to describe flow velocity waveforms of abdominal arteries in the appropriate- and small-for-gestational-age fetus. Splenic artery, superior mesenteric artery, hepatic artery and renal artery velocity waveforms were obtained from 57 appropriate-for-gestational-age and nine small-for-gestational-age fetuses with color flow Doppler ultrasonography. The pulsatility index was used to quantify the arterial waveforms. Repeated measure analysis of variance indicated significant differences in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 0 publications
3
23
0
1
Order By: Relevance
“…Although the sparing effect of the splenic, adrenal, coronary and cerebral arteries has been reported in response to chronic fetal hypoxia [19][20][21], the sparing effect of splanchic circulation has rarely been described. Mari et al [22] showed a decreased PI in the abdominal arteries of SGA fetuses, compared with AGA control fetuses. Recently, compensatory elevated blood flow in the hepatic artery of SGA fetuses was reported [23].…”
Section: Discussionmentioning
confidence: 94%
“…Although the sparing effect of the splenic, adrenal, coronary and cerebral arteries has been reported in response to chronic fetal hypoxia [19][20][21], the sparing effect of splanchic circulation has rarely been described. Mari et al [22] showed a decreased PI in the abdominal arteries of SGA fetuses, compared with AGA control fetuses. Recently, compensatory elevated blood flow in the hepatic artery of SGA fetuses was reported [23].…”
Section: Discussionmentioning
confidence: 94%
“…Previous observations have shown vasodilation in the adrenal artery of fetuses with chronic hypoxemia [13][14][15]. These studies describe the presence of vasodilatation in the fetal adrenal artery as being associated with prematurity, higher Cesarean section rates, fetal distress detected by cardiotocography, and longer time periods spent in neonatal intensive care units.…”
Section: Discussionmentioning
confidence: 65%
“…The only reference range of the fetal mean adrenal artery PI was described by Mari et al [15]. They assessed 131 singleton pregnancies and observed that PI values decreased with increasing gestational age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fetuses that show these early Doppler changes are at increased risk for hypoxemia, while the pH is usually maintained in the normal range [27]. Concurrently blood flow resistance in peripheral pulmonary arteries [28], celiac axis [29], mesenteric vessels [30], renal [31], femoral and iliac arteries [32] may be elevated. Individual vital organs such as the adrenal glands [33] and spleen [34] may show evidence of enhanced blood flow.…”
Section: Early Doppler Changesmentioning
confidence: 99%